Transition to the circular economy in the Brazilian cosmetics sector: A case study of Natura &Co in light of the National Solid Waste Policy (Research, Society and Development, 2025)
Overcoming the linear production model is urgent for high environmental impact sectors, such as cosmetics, which in Brazil are under pressure from the National Solid Waste Policy (PNRS). Given this context, this article aims to analyze the opportunities and challenges of the transition to a Circular Economy (CE) in this industry, examining its relationship with the instruments of the PNRS. To this end, a qualitative methodology is adopted, based on a case study of Natura &Co, complemented by bibliographic review and documentary analysis. The results reveal that the CE, when articulated with the PNRS instruments, can generate concrete opportunities such as fostering innovation, increasing competitiveness, and reducing costs in the long term, enabled by initiatives like the use of refills and the implementation of reverse logistics. However, the transition faces structural challenges, such as the high burden of initial investment for smaller companies, the limitation of the national recycling infrastructure, low consumer adherence to new practices, and the very complexity of regulatory frameworks. It is concluded that, although the transition to a CE is technically viable and shows specific advances, its consolidation on a large scale depends on multisectoral coordinated action that goes beyond the legal sphere and faces questions about its ability to break with the logic of linear growth, requiring parallel advances in recycling and reuse infrastructure, business innovation, and a broader cultural transformation.